The startle reaction to an acoustic stimulus in the rat: the effect of noradrenaline administered by microinjection into the pontomedullary reticular formation - Pavlásek, J (Physiologia Bohemoslovaca, 1989)
The effect of the local administration of noradrenaline (NA) by microinjection into the pontomedullary reticular formation on the startle reaction (SR) evoked by an acoustic stimulus was studied in waking, non-immobilized rats. NA (10(-6) mol.l-1 in 2.5 microliters artificial cerebrospinal fluid) was administered 21 times to five animals in 13 experiments. In nine cases (43%), a significant change in the mean amplitude of the SR to a series of 30 stimuli (recorded in the third minute after administering NA) was observed; in eight cases (38%) it rose and in only one (5%) it fell. Binomial statistics confirmed the preponderance of results with an increase in SR amplitude. The results indicated that the potentiating effect of NA could actively help to regulate the function of the pontomedullary part of the neuronal circuit for the acoustic SR.
Keywords: Rats, Inbred Strains; Medulla Oblongata; mikroinjekce; noradrenalin; Norepinephrine; Pons; pons; medulla oblongata; inbrední kmeny potkanů; úleková reakce; akustická stimulace; retikulární formace; krysa rodu Rattus; Microinjections; Animals; Reticular Formation; ženské pohlaví; zvířata; Acoustic Stimulation; Rats; Reflex, Startle; Female